52.5k views
1 vote
Solve for x. y=c(x+b) Enter your answer in the box.x =

User Woohyung
by
5.3k points

2 Answers

6 votes

Answer:

x = (y-cb)/c

Explanation:

First expand the right side :

y = cx + cb

Subtract cb from both sides :

y - cb = cx

Divide both sides by c :

(y-cb)/c = x

x = (y-cb)/c

Hope this helped and have a good day

User Hellectronic
by
5.0k points
5 votes

Ok, so

Here we have the expression:


y=c(x+b)

We want to solve this expression for x.

The first thing we're going to do is to distribute the letter outside the bracket in the terms inside of it.

This is:


y=cx+cb

Now, we could substract "cb" to both sides of the equation:


y-cb=cx

And then, divide by c:


x=(y-cb)/(c)

And the solution for x will be:

x = (y-cb)/c

User Jmarceli
by
6.0k points